2010
DOI: 10.1007/s12032-010-9522-3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous over activation of EGFR, telomerase (h TERT), and cyclin D1 correlates with advanced disease in larynx squamous cell carcinoma: a tissue microarray analysis

Abstract: Overexpression of Epidermal Growth Factor Receptor (EGFR) and also of cell cycle control proteins, such as cyclin D1 is a frequent event in squamous cell carcinoma of the larynx (LSSC). Our aim was to correlate their protein levels with telomerase catalytic subunit (h-TERT) expression. Using tissue microarray technology, fifty-five paraffin embedded histologically confirmed primary LSSCs and also ten dysplastic lesions were cored at a diameter of 1.5 mm. Immunohistochemistry (IHC) was performed by the use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Recently, Heeg et al reported that EGFR leads to the phosphorylation of hTERT and regulates telomerase activity through the PI3K/ AKT signaling pathway (31). Combined EGFR, cyclin D1 and hTERT protein expression was correlated with an aggressive phenotype in squamous cell carcinoma of the larynx (32). In the present study, a significant correlation was found between the expression of EGFR mRNA and telomerase activity.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, Heeg et al reported that EGFR leads to the phosphorylation of hTERT and regulates telomerase activity through the PI3K/ AKT signaling pathway (31). Combined EGFR, cyclin D1 and hTERT protein expression was correlated with an aggressive phenotype in squamous cell carcinoma of the larynx (32). In the present study, a significant correlation was found between the expression of EGFR mRNA and telomerase activity.…”
Section: Discussionsupporting
confidence: 67%
“…Such a combined pattern was described recently as an independent marker of worse overall survival . Previous studies using immunohistochemistry for assessment of EGFR protein expression report EGFR overexpression in most (≥80%) oral and other head and neck SCC . This limits the value of EGFR protein expression as a prognostic or predictive biomarker and makes comparison of protein expression with EGFR copy number changes more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR mutation is rare in head and neck SCC (0–7.3%) and has been detected only in laryngeal carcinoma . EGFR protein overexpression has been detected using immunohistochemistry in most (≥80%) oral and other head and neck SCC, but its prognostic and predictive value is controversial . Increased EGFR gene copy number was detected in up to 58% of oral SCC, but correlation of increased gene copy number with survival or treatment response generated conflicting results in patients with head and neck SCC …”
Section: Introductionmentioning
confidence: 99%
“…Telomerase can be associated, alone or together with other markers, with a more aggressive phenotype and behavior in HNSCC. Several studies have, indeed, reported that TERT mRNA levels and telomerase activity are higher in poorly differentiated SCC [ 63 , 126 , 143 , 146 , 166 – 169 ], increase with tumor stage [ 63 , 131 , 142 , 166 ], and are associated with lymph node involvement [ 63 , 126 , 131 , 137 , 139 , 170 ] or extracapsular extension of lymph node metastases [ 125 ]. Numerous studies have analyzed telomerase’s ability to predict outcome (Table 1 ) [ 46 , 63 , 125 , 127 , 130 , 136 , 139 , 140 , 144 , 171 177 ], and most have reported a correlation between increased telomerase expression and activity and a reduced response to treatment and a higher rate of regional and distant metastases ultimately resulting in poor clinical outcome [ 63 , 125 , 127 , 136 , 144 , 171 , 173 176 ].…”
Section: Telomerase In Hnsccmentioning
confidence: 99%